Cynomolgus monkeys (Macaca fascicularis) experimentally and naturally infected with hepatitis E virus: The bone marrow as a possible new viral target - Bottino, Fernanda de Oliveira (2018)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Desenvolvimento Tecnológico em Virologia. Rio de Janeiro, RJ. Brasil.